2019
DOI: 10.2147/orr.s188678
|View full text |Cite
|
Sign up to set email alerts
|

<p>High IL-6 level as a marker of lumbar osteoarthritis in patients older than 55 years with low back pain</p>

Abstract: Background Low back pain (LBP) is a common clinical condition encountered by most physicians, but the cause and risk factors are still unclear. Cytokines such as IL-6 play an important role in cartilage degeneration, but the role of IL-6 in osteoarthritis (OA) is still debatable. Herein, we aimed to determine the association between high IL-6 levels and lumbar OA in patients older than 55 years with LBP. Method This was a case–control study. Patients included 10 men and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Chronic inflammatory progression in OA is regulated through multiple cytokine networks, including the IL-6 pathway. Previous research has documented increased IL-6 concentrations in sera and synovial fluid from OA patients (Pratama, Suyasa, Astawa, & Lestari, 2019). Moreover, inhalation of air pollutants leads to oxidative damage and inflammation, and cytotoxic responses in the body, including cellular IL-6 production (Chau & Wang, 2020).…”
mentioning
confidence: 99%
“…Chronic inflammatory progression in OA is regulated through multiple cytokine networks, including the IL-6 pathway. Previous research has documented increased IL-6 concentrations in sera and synovial fluid from OA patients (Pratama, Suyasa, Astawa, & Lestari, 2019). Moreover, inhalation of air pollutants leads to oxidative damage and inflammation, and cytotoxic responses in the body, including cellular IL-6 production (Chau & Wang, 2020).…”
mentioning
confidence: 99%
“…IL6, derived from macrophages, chondrocytes, and osteoclasts can increase inflammatory cells in synovial tissue and stimulate chondrocyte proliferation. Dewa GK et al found that the incidence of lumbar OA in patients with high levels of IL6 was five times higher than in patients with low levels of IL6, suggesting that IL6 is closely related to the occurrence of OA ( Pratama et al, 2019 ). TNF, derived from macrophages and chondrocytes, serves as an indispensable mediator in the degradation of the cartilage matrix and is closely related to synovitis, and it has been widely reported that many drugs interact with TNF to make an effect on OA.…”
Section: Discussionmentioning
confidence: 99%
“…(79,80) Certainly, findings that Tai Chi Chih decreased high plasma levels of IL-6, (42) indicates that Tai Chi might be a valuable therapy for alleviating systemic infl ammation and arresting OA progression. (81)…”
Section: Infl Ammationmentioning
confidence: 99%